Religion, religiosity and materialism - Lau, Ung Ing (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Materialism is a consumer value and believed to be influenced by an individual's religion and its religiosity. This study investigates the significant difference of religion and religiosity towards materialism in Malaysia. The study was conducted by collecting primary data through self administrated questionnaires from one of the local university in Malaysia. Collected data was analyzed through factor analysis, reliability test, frequency, mean, ANOVA and T-tesy The study demonstrated that there is significant difference by religiosity; Buddhist religiosity; low intra / low inter-personal religiosity; and Muslim intra-personal religiosity towards certain materialism measures. There is no significant difference exhibited between religion and materialism; and inter-personal religiosity and materialism. Data collection for the study could be extended to a wider geographical area. In addition to that, elements such as economic factors, political factors and globalization factors should consider being included into future study. Based on the study's findings, marketers can take note on the country's materialism scenario, and do consumer segmenting appropriately. Nevertheless, marketers can also adjust their communication pattern towards their consumers in order to find tune to generate a better sales persuasion strategy.